2011
DOI: 10.1089/oli.2010.0273
|View full text |Cite
|
Sign up to set email alerts
|

Oligo/Polynucleotide-Based Gene Modification: Strategies and Therapeutic Potential

Abstract: Oligonucleotide- and polynucleotide-based gene modification strategies were developed as an alternative to transgene-based and classical gene targeting-based gene therapy approaches for treatment of genetic disorders. Unlike the transgene-based strategies, oligo/polynucleotide gene targeting approaches maintain gene integrity and the relationship between the protein coding and gene-specific regulatory sequences. Oligo/polynucleotide-based gene modification also has several advantages over classical vector-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 258 publications
(292 reference statements)
0
23
0
Order By: Relevance
“…Successful targeted chromosomal deletions, duplications and inversions using ZFN [5, 9, 2325] prompt us to investigate the possibility of targeted GSV using TALEN. We have previously shown that simultaneous expression of two TALENs could mediate heritable 792 bp segment deletion in silkworm, B. mori [11], which was also supported by similar investigations in livestock [12] and zebrafish [26].…”
Section: Discussionmentioning
confidence: 99%
“…Successful targeted chromosomal deletions, duplications and inversions using ZFN [5, 9, 2325] prompt us to investigate the possibility of targeted GSV using TALEN. We have previously shown that simultaneous expression of two TALENs could mediate heritable 792 bp segment deletion in silkworm, B. mori [11], which was also supported by similar investigations in livestock [12] and zebrafish [26].…”
Section: Discussionmentioning
confidence: 99%
“…RDOs are a class of oligonucleotides used for gene targeting with a correction efficiency of approximately 50 %; however, the reproducibility of these studies has been limited in mammalian systems (Sargent et al 2011). TFOs are ssODNs that are typically 10-40 nt in length and bind to specific regions in duplex DNA as a third strand to form a triple helix.…”
Section: Missense Mutationsmentioning
confidence: 99%
“…TFOs are ssODNs that are typically 10-40 nt in length and bind to specific regions in duplex DNA as a third strand to form a triple helix. TFOs act in polypurine or polypyrimidine regions of DNA and bind DNA via Hoogsteen hydrogen bonds (Sargent et al 2011, Pauwels et al 2014.…”
Section: Missense Mutationsmentioning
confidence: 99%
“…Our current knowledge on the basic mechanisms of OTNE originates from several studies performed exclusively on microorganisms and mammalian cells (Bonner and Kmiec 2009;Engstrom and Kmiec 2007;Sargent et al 2011). According to the widely accepted general model, after invading the targeted site of the duplex DNA, SDOs are hybridized to the complementary strand through transient D-loop formation.…”
Section: Introductionmentioning
confidence: 99%